Effect of playing position, passage duration and starting status on the most demanding passages of match play in professional football - Martín-Fuentes, I.; Oliva-Lozano, J. M.; Fortes, V.; Muyor, J. M. (Research in Sports Medicine, 2021)
The aims of this research were to analyse the effect that different playing positions, passage durations and starting status had on the most demanding passages (MDP) of play in professional football matches. Players were categorized by positions and the MDP of distance (DIS), high-speed running distance (HSRD) and sprinting distance (SPD) were analysed for four passage durations (1, 3, 5 and 10minutes). The results indicated that DIS (p <0.001), HSRD (p <0.001) and SPD (p <0.001) covered per minute decreased as the passage durations increased for all positions. Regarding the playing position, it had a significant effect on the DIS (p <0.001), HSRD (p <0.001) and SPD (p <0.001) covered. In addition, although the results reported that the starting status had no significant effect on the DIS (p =0.36) covered, it had a statistically significant effect on the HSRD (p =0.01) and SPD (p <0.001) covered. Coaching and medical departments should consider the impact that these variables have on players` performance when designing training drills aimed at preparing the player for the competitive demands.